Designing a Structural Equation Model of Physical Activity Level, Job Burnout, and Effectiveness of Police Academy Officers in Iraq - Falih Hasan, Ahmed; Askari, AhmadReza; Jabbar Naser, Abduljaleel; Serjuei, Zahra; khorvash , Majid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aimed to design a structural equation model to examine the relationships between physical activity levels, job burnout, and the effectiveness of Iraq Police Academy officers. Methodology: The research was applied, descriptive, and survey-based, utilizing structural equation modeling (SEM) to analyze data. The sample consisted of 384 police officers from the Iraq Police Academy, selected through random sampling based on the Krejcie and Morgan table. Data were collected using standardized questionnaires: the Physical Activity Questionnaire by Askari et al. (2013), the Maslach Burnout Inventory (MBI), and the Effectiveness Questionnaire by Vandewalle (2000). The validity of the scales was confirmed using confirmatory factor analysis, and reliability was assessed using Cronbach’s alpha. SEM analysis was conducted using LISREL software. Findings: The results showed that the levels of physical activity and effectiveness among Iraq Police Academy officers were above average, while job burnout levels were below average, indicating a favorable status. The analysis confirmed a significant positive relationship between physical activity and officer effectiveness, with higher physical activity levels associated with improved performance. Additionally, job burnout was found to mediate the relationship between physical activity and effectiveness, highlighting the importance of managing job burnout to enhance officer performance. The model demonstrated an adequate fit with the data. Conclusion: The study concluded that promoting physical activity can positively influence the effectiveness of police officers while reducing job burnout. Effective management strategies, including regular exercise programs and initiatives to alleviate job burnout, are essential for improving officer well-being and organizational performance.